2009
DOI: 10.1080/01140670909510251
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of peel and flesh in ‘GoldRush’ and ‘Fiorina’ scab‐resistant apple (Malus domestica) cultivars

Abstract: In the human diet, apples (Malus domestica) are the most consumed fruit worldwide throughout the whole year and are valued for their organoleptic characteristics (aroma, taste, and flavour). Apples are also an important source of phytochemicals, represented by flavonols, flavanols, cinnamic acid, dihydrochalcones, and anthocyanins, which have a known antioxidant activity that can prevent or reduce the insurgence of several chronic and degenerative diseases. These compounds have been found especially in the pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
(33 reference statements)
7
13
0
1
Order By: Relevance
“…As reported by several authors,3, 4, 12, 35 peel was richer than pulp in single phenolic compounds as well as in total polyphenolics. Apple peel has a total phenolic content 3–7.5 times higher than pulp.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…As reported by several authors,3, 4, 12, 35 peel was richer than pulp in single phenolic compounds as well as in total polyphenolics. Apple peel has a total phenolic content 3–7.5 times higher than pulp.…”
Section: Resultssupporting
confidence: 65%
“…The reason for that can probably be found in the great genetic differences between the apple cultivars analysed. That cultivars can also have an influence on the amount of phenolics has been reported by many papers 3, 4, 13, 26, 35. In the case of leaves, year and cultivar were also taken into account, as well as dates, since we obtained data from six different sampling dates (Table 7).…”
Section: Resultsmentioning
confidence: 92%
“…Several times more phenolic compounds are found in the peel than in apple flesh (Wolfe et al 2003, Drogoudi et al 2008, Leccese et al 2009). High content of phenols was detected in apple juices as well (Lachman et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…There are studies which indicated that 80% of polyphenols are found in apple peel (Leccese et al, 2009), whose total antioxidant capacity is five-to-six-fold higher than that of apple flesh; The health advantages of apple peels, like cardioprotective and anticancer properties, are correlated with the presence of flavonols, anthocyanins, flavan-3-ols, phenolic acids and dihydrochalcones (Boyer and Liu, 2004). Compared with the flesh, the peel contains specific flavonoids, such as quercetin glycosides (Rupasinghe and Kean, 2008).…”
Section: Introductionmentioning
confidence: 99%